Miskonsepsi Pemahaman Materi Bangun Datar dengan Penerapan Teori Polya di PGMI-3 UIN Sumatera Utara - Adien Inayah; Rora Rizky Wandini (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
This article aims to identify misconceptions that occur in solving flat shape problems using the application of Polya Theory among PGMI-3 students at UIN North Sumatra. Polya theory is a systematic approach used to solve mathematical problems and other problems. This approach is designed to assist students and mathematicians in designing effective problem-solving strategies. Even though you have used Polya Theory, misconceptions may also occur in understanding and working on flat shape problems. The type of research used is qualitative descriptive research with the research subjects being PGMI-3 UIN North Sumatra students. The research results show that there are several misconceptions involving understanding the steps of Polya Theory and the placement of length units. Of the 6 students who were subjects, only 2 students had an understanding of the placement of units of length, while the other 4 students experienced misconceptions with a percentage of 34%. Likewise, understanding the steps of Polya Theory, only 4 students understood it while 2 more experienced misconceptions with a percentage of 66%.